KINERJA PEGAWAI UNIVERSITAS PADJADJARAN BANDUNG: IKLIM KERJA DAN MOTIVASI KERJA - Rahsel, Yoeyong (Jurnal Manajemen Magister Darmajaya, 2017)
In line with globalization era, every university are demanded to prepare itâself become a ready university of compete with other company. The factor that partakes to achieve that purpose is a quality of human resources. Many kind of labour problems, one of them is low of work performance. The low of employeeâs work performance could be influenced by motivation and work climate. Be aware of the important motivation and work climate with supported the increasing of employeeâs work performance, therefore it need and effort to applied the motivation seriously and created the work climate condusifly. With motivation level and work climate increased, it would influence the employeeâs work performance. From that fact, the purpose this research was conducted to know how high is the motivation level, work climate and employeeâs work performance and how big is the influence of motivation and work climate to employeeâs work performance at general administration of Padjadjaran University. The research method which used is descriptive survey and explanatory survey. The population of this research was taken from all at general administration University Of Padjadjaran employeeâs which number in 225 person. The sample in this research amount to 65 person. In order to know how big the motivation and work climate influence to the employeeâs work performance is used double linear regression because the independent variable is more than two variables. Based on hypothesis and the writerâs research result, found out that there is a positive influence of motivation and work climate to employeeâs work performance. Based on anova table showed the influence of motivation and work climate to employeeâs work performance at general administration University Of Padjadjaran thus, the writerâs hypothesis was proven and acceptable. The recomendation which was given by the write to general administration University Of Padjadjaran is the increasing of employeeâs work performance would be reached if the university capable of implementhing the motivation accurately by giving the quidance, support and corporation from superior to the lower class to capable of implementhing their job optimum the conductive work climate is needed by the employee through a good relationship and communication, those believes and openness become a capital for the employee to reach the highest work performance.Â Keywords : Work Climate, Work Motivation, Performance work, Explanatory Survey